Incidence of mycobiota and aflatoxin B1 in Algerian feed - Bouti, Karima; Mimoune, Nouara Ait; Mokrane, Salim; Djemouai, Nadjette; Verheecke-Vaessen, Carol; Mathieu, Florence; Riba, Amar (Inderscience, 2022)
The presence of fungi and aflatoxin B1 (AFB1) in 101 animal feed samples randomly collected from different vendors and factories in Algeria was investigated. For fungi, the main genera isolated were Aspergillus, Penicillium and Fusarium. Furthermore, the 459 strains of Aspergillus section Flavi were screened for their ability to produce aflatoxins and cyclopiazonic acid. 49% of the strains produced AFB1. The highest incidence of aflatoxigenic strains was recorded in maize (61%) and ground poultry feed (60%). The presence of AFB1 in feed samples was evaluated using HPLC-FLD. The obtained data showed that 36.6% of samples were contaminated in the range of 0.34 to 171.06 μg/kg. Six samples exceeded the Algerian maximum limit of 20 µg/kg for AFB1. This study highlights the potential presence of aflatoxigenic strains belonging to section Flavi and AFB1 in animal feed at post-harvest in Algeria, strategic information for the Algerian policies makers.
Keywords: Animal feed; Aspergillus section Flavi; aflatoxin B1; Algeria